STUNTING PREVENTION EDUCATION THROUGH THE STUNTING REDUCTION ACCELERATION PROGRAM AT THE WOMEN'S EMPOWERMENT, CHILD PROTECTION, POPULATION CONTROL AND FAMILY PLANNING OFFICE OF TANA TORAJA DISTRICT - Parasila, Natan; Sjamsuddin, Sjamsiar; Nuh, Mohammad (Erudio Journal of Educational Innovation, 2024)
The Stunting Reduction Acceleration Program is a national priority program in intervening stunting throughout Indonesia including Tana Toraja district as the highest stunting prevalence district in South Sulawesi. Based on the 2022 Electronic Application for Community-Based Nutrition Recording and Reporting (e-PPGBM), Tana Toraja district is the third highest stunting district in South Sulawesi province and the second highest stunting district based on the 2022 Indonesian Nutrition Status Survey (SSGI) results. The results showed that stunting prevention education through the accelerated stunting reduction program at the Office of Women's Empowerment, Child Protection, Population Control and Family Planning of Tana Toraja Regency has been carried out optimally based on the results of data analysis using three indicators from Soren C Winter, namely inter-organizational behavior, implementor behavior or lower-level bureaucracy and target group behavior. Indicators of inter-organizational behavior and indicators of implementor behavior or lower-level bureaucracy are carried out, but indicators of target group behavior are not optimally implemented due to the fact that there are still some people who refuse to receive assistance and participate in program activities because they consider stunting a disgrace and it was found that there are still some people who stunt their children who are not stunted with the motivation to get food assistance. This study uses a qualitative research method with a descriptive approach with the research objective to determine the extent of the implementation of the accelerated stunting reduction program at the Tana Toraja District Health Office.